Effect of smoke-free home and workplace policies on second-hand smoke exposure levels in children: an evidence summary. Issue 4 (August 2010) - Kabir, Zubair; Alpert, Hillel R; Goodman, Patrick G; Haw, Sally; Behm, Ilan; Connolly, Gregory N; Gupta, Prakash C; Clancy, Luke
Second-hand smoke (SHS) is a major avoidable cause of developmental and respiratory disease and premature death among children worldwide. SHS is a 'Class A' carcinogen, and there is no safe level of SHS exposure. Almost 700 million children worldwide are exposed daily to SHS at home. This article reviews and summarizes evidence based on available studies that report on 'voluntary' home smoking restrictions and their effects on SHS exposure levels in children aged 0–17 years. All potentially relevant publications within a 10-year period (January 2000–April 2010) were identified (n = 19 full-text articles) through comprehensive database searches. In general, voluntary household smoking restrictions reported a significant reduction in childhood SHS exposure ranging between 20–50% reductions, using both self-reported and biological measures. Mandated comprehensive workplace and enclosed public smoke-free policies also suggested an apparent benefit in some specific pediatric health encounters, namely, decreased preterm birth risks and reduced emergency hospital visits owing to asthma.